2018
DOI: 10.1002/jcp.27414
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing antiangiogenesis therapy: The significant role of hypoxia‐inducible factor and MET in development of resistance to anti‐vascular endothelial growth factor‐targeted therapies

Abstract: It is now fully recognized that along with multiple physiological functions, angiogenesis is also involved in the fundamental process and pathobiology of several disorders including cancer. Recent studies have fully established the role of angiogenesis in cancer progression as well as invasion and metastasis. Consequently, many therapeutic agents such as monoclonal antibodies targeting angiogenesis pathway have been introduced in clinic with the hope for improving the outcomes of cancer therapy. Bevacizumab (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 103 publications
0
27
0
Order By: Relevance
“…This is likely mediated through induction of hypoxia by the anti-angiogenic therapy, resulting in compensatory upregulation of both VEGF and VEGF-independent angiogenesis pathways (119,122). Proposed resistance mechanisms include vascular mimicry, enhancement of invasive potential, recruitment of bone marrow-derived precursor endothelial cells, and promotion of alternative proangiogenic pathways (5,39,42,123), which are of interest as potential therapeutic targets in breast cancer.…”
Section: Therapeutic Strategies Targeting Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely mediated through induction of hypoxia by the anti-angiogenic therapy, resulting in compensatory upregulation of both VEGF and VEGF-independent angiogenesis pathways (119,122). Proposed resistance mechanisms include vascular mimicry, enhancement of invasive potential, recruitment of bone marrow-derived precursor endothelial cells, and promotion of alternative proangiogenic pathways (5,39,42,123), which are of interest as potential therapeutic targets in breast cancer.…”
Section: Therapeutic Strategies Targeting Angiogenesismentioning
confidence: 99%
“…Hypoxia created by VEGF pathway inhibitors correlates with upregulation of the MET oncogene, that promotes invasive behavior and is an adverse prognostic factor in breast cancer (42,123,124). Cabozantinib (XL-184) is a potent oral inhibitor of MET and VEGFR-2, and phase II trials showed mixed clinical benefit rates (0-34%) in metastatic TNBC (125,126).…”
Section: Therapeutic Strategies Targeting Angiogenesismentioning
confidence: 99%
“…Neo-angiogenesis is a critical step in tumor progression as it enhances tumor growth and cancer cell metastasis. The concept of anti-angiogenic therapy, i.e., inhibiting pro-angiogenic factors, has remained disappointing, in part due to acquired resistance [84]. The role of integrin in endothelial cell migration and survival and in angiogenesis has been widely described [85].…”
Section: β1 Integrinsmentioning
confidence: 99%
“…Finally, the phosphoinositide 3 kinase (PI3K)/Akt signaling pathway is activated via multiple pathways. The activation of Akt is associated with EC survival and the upregulation of endothelial nitric oxide synthase (eNOS) which further increases vessel permeability 9,13,14 (Figure 1).…”
Section: Tumor Angiogenesis In Nsclcmentioning
confidence: 99%
“…26 Hypoxia induces the overexpression of VEGF-A directly through HIFs, which can bind to the promoter element of VEGF-A and initiate the transcription of VEGF-A. 14 The activation of epidermal growth factor receptor (EGFR) is also a pro-angiogenic factor, as it can upregulate the production and secretion of VEGF. 27 Although there are no valid predictive biomarkers of response to treatment with anti-angiogenetic inhibitors, it was reported that the expression of VEGF-A was increased in EGFRmutant NSCLC compared with EGFR-wild type.…”
Section: Tumor Angiogenesis In Nsclcmentioning
confidence: 99%